2013
DOI: 10.1302/0301-620x.95b12.32146
|View full text |Cite
|
Sign up to set email alerts
|

Long-term follow-up of mobile-bearing total ankle replacement in patients with inflammatory joint disease

Abstract: Little is known about the long-term outcome of mobile-bearing total ankle replacement (TAR) in the treatment of end-stage arthritis of the ankle, and in particular for patients with inflammatory joint disease. The aim of this study was to assess the minimum ten-year outcome of TAR in this group of patients. We prospectively followed 76 patients (93 TARs) who underwent surgery between 1988 and 1999. No patients were lost to follow-up. At latest follow-up at a mean of 14.8 years (10.7 to 22.8), 30 patients (39 T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
7
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(9 citation statements)
references
References 38 publications
2
7
0
Order By: Relevance
“…As haemophilic arthropathy and inflammatory joint disease share some pathophysiological aspects, comparison seems particularly applicable. In the light of this, the present study's 15‐year implant survival of 70% nearly accords with the 73% reported by Kraal et al who examined 93 cases of TAR in inflammatory joint disease. Bartel et al reported 5‐ and 10‐year survival rates of 87% and 81% (vs 94% and 85%), based on data of all 6 listed national joint registries including 5152 primary TARs in general populations.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…As haemophilic arthropathy and inflammatory joint disease share some pathophysiological aspects, comparison seems particularly applicable. In the light of this, the present study's 15‐year implant survival of 70% nearly accords with the 73% reported by Kraal et al who examined 93 cases of TAR in inflammatory joint disease. Bartel et al reported 5‐ and 10‐year survival rates of 87% and 81% (vs 94% and 85%), based on data of all 6 listed national joint registries including 5152 primary TARs in general populations.…”
Section: Discussionsupporting
confidence: 91%
“…Corresponding studies reporting long‐term outcomes in haemophiliacs are missing. However, the here reported long‐term survival is comparable both to the results in patients with inflammatory joint disease and to the results in a general population. As haemophilic arthropathy and inflammatory joint disease share some pathophysiological aspects, comparison seems particularly applicable.…”
Section: Discussionsupporting
confidence: 85%
“…24,25,31 Other common complications quoted in literature include infections (3.2% to 13%), wound healing issues (1.6% to 14%), and postsurgical pain (2% to 4%). [6][7][8][9][23][24][25][26][27][28][29][30][31] Although these complications are not reflected in the current study, they are common reasons for readmission.…”
Section: Discussionmentioning
confidence: 99%
“…Taken collectively, total ankle replacement requires precise implantation because mobile-bearing UHMWPE inserts or more incongruity between the fixed-bearing UHMWPE insert and talar component geometry are incapable of predictably accommodating appreciable malalignment. Finally, the withdrawal in 2009 of the B€ uechel-Pappas total ankle system (Endotec, South Orange, NJ) (83), which was the predicate mobilebearing design and had good 20-year patient outcomes and survivorship (84), combined with the good 14-year patient outcomes and survivorship with the ESKA fixed-bearing total ankle (GmbH & Co, L€ ubeck, Germany) (85), and lack of clinically significant differences in outcomes or survivorship between mobile-and fixed-bearing prosthesis types (16) indicates that the bearing type should not be the main criteria for surgeon adoption of a particular prosthesis.…”
Section: Discussionmentioning
confidence: 99%